Focal cutaneous telangiectasia in a young dog of probable congenital origin. Issue 6 (9th September 2022) - Ueyama, Akira; Hoshino, Tomoya; Asakawa, Midori Goto; Shimada, Toshio; Nagata, Masahiko
Abstract: Background: Idiopathic cutaneous telangiectasia has been rarely described in the dog. Objectives: We present the first case of idiopathic focal cutaneous telangiectasia in a young dog of probable congenital origin. Methods: An 18‐month‐old spayed female Maltese dog presented with demarcated erythema of the skin on the right thorax. The lesion consisted of scattered, florid, ramified macules with mild dermatrophia and desquamation. The lesion was examined with histopathology and immunohistochemistry using antibodies for alfa‐SMA. Results: Diascopy revealed a blanchable lesion. Tortuous capillary expansion was observed by dermoscopy. The histopathological examination revealed dilated but otherwise unremarkable capillaries in the superficial dermis compatible with cutaneous telangiectasia. The lesion was followed up over a 3‐year period and had essentially remained stable. Other vascular anomalies displaying similarities with telangiectasia are discussed. Conclusions: In human vascular anomalies, this case would be presumably classified as 'telangiectasia' by the International Society for the Study of Vascular Anomalies. We propose that primary cutaneous telangiectasia should be included in the list of differential diagnoses for this type of lesions in dogs. We also suggest that dermoscopy would be a valuable tool for the identification of vascular anomalies in dogs. Abstract : This report describes the first case of a dog with an early‐onset capillary disorder characterised by focal telangiectasia. Dermoscopic image showing a reticular appearance of capillary expansion